You are on page 1of 8

# Math 2120 - Analysis and Mathematical Methods I

## Semester 1, Academic Year 2012/2013

FIRST COURSEWORK EXAM (15%)
Monday 8th October 2012
Instructions to Candidates: Answer any two questions
Time Limit: 1 hour
SOLUTIONS

## 1. Answer the following sequence question showing all your working:

(a) Provide a formal de…nition for the limit of a sequence. Use this de…nition to
2n + 3 2
prove that the sequence ; n 1 converges to a limit :
3n + 4 3
[8 marks]
SOLUTION: The sequence fan g1 n=1 converges to a limit L if given any > 0;
there exists a N (positive integer) such that jan Lj < for n > N:
SOLUTION: We wish to prove that given any > 0; there exists a N (positive
2n + 3 2
integer) such that < for n > N:
3n + 4 3
Consider
2n + 3 2 3 (2n + 3) 2 (3n + 4) 1
= =
3n + 4 3 3 (3n + 4) 3 (3n + 4)
1 1
< < = for n > N
9n 9N
1 2n + 3 2
Hence for any > 0; there exists a N = such that < for n > N:
9 3n + 4 3
(b) Consider the sequence of positive terms fan g ; n 1 de…ned as
4 + 3an
a1 = 1; an+1 = ; n 1:
3 + 2an
1. Use mathematical induction to prove that the sequence is increasing.
SOLUTION: We need to prove that an+1 an 0 for all n 1:
Case n = 1; we get
4 + 3a1 7
a2 a1 = 1= 1>0
3 + 2a1 5

1
hence it is true for n = 1: Assume that it is true for n = k; i.e. that

## ak+1 ak 0 for all k 1:

Consider n = k + 1;
4 + 3ak+1 4 + 3ak
ak+2 ak+1 =
3 + 2ak+1 3 + 2ak
This simpli…es to
ak+1 ak
ak+2 ak+1 =
(3 + 2ak+1 ) (3 + 2ak )
Now since we know that ak > 0 for all k since this is a sequence of positive
terms, as we have that ak+1 ak 0 for all k 1; it follows that

ak+2 ak+1 0

## and therefore by mathematical induction, we can conclude that an+1 an 0

for all n 1:
2. Use mathematical induction to prove that the sequence is bounded above by
3
:
2
3
SOLUTION: We need to prove that an 0 for all n 1: Consider the
2
case n = 1; we have
3 3
a1 =1 <0
2 2
hence it is true for n = 1: Assume it is true for n = k; i.e. that
3
ak 0 for all k 1
2
Consider the case n = k + 1; i.e.
3 4 + 3ak 3 8 + 6ak 9 6ak 1
ak+1 = = =
2 3 + 2ak 2 2 (3 + 2ak ) 2 (3 + 2ak )
However, we know that all the terms of this sequence are positive, which
means
3
ak+1 <0
2
and therefore the case n = k + 1 is true, and by mathematical induction, we
3
have that an 0 for all n 1:
2

2
3. Find the supremum of the sequence, justifying your answer completely.
SOLUTION: By the increasing sequence theorem, this sequence is convergent
to a limit L which is equivalent to the supremum. Therefore
L= lim an = lim an+1
n!1 n!1
4+3an
Taking the limit of an+1 = 3+2an
as n ! 1; we obtain
4 + 3L p
L= )L= 2
3 + 2L
As
p this sequence is one of positive terms, we have therefore a supremum of
2:
[12 marks]

2. (a) State the integral test and the alternating series test for in…nite series. Given
1
that the function f (n) = p is continuous, positively valued and decreasing for
n ln n
X1
( 1)n
n 3, prove that the series p is convergent. Is the convergence of this
n = 3 n ln n
series absolute or conditional? Justify your answer completely:
[10 marks]
SOLUTION: Integral Test: Let f (x) be a continuous, decreasing, positive valued
function for x 1: Then the in…nite series
X
1
f (n) = f (1) + f (2) + f (3) + :::
n = 1
R1
is convergent if and only if 1
f (x) dx is …nite, and is divergent if
Z b
Lim f (x)dx = +1:
b ! 1 1

P
1
SOLUTION: Alternating Series Test: Consider an alternating series ( 1)n+1 an ;
n = 1
where an 0 and an+1 an for all positive integers n: If lim an = 0; then the
n ! 1
alternating series is convergent.
X1
( 1)n 1
SOLUTION: Consider the series p : As the function f (n) = p is
n = 3 n ln n n ln n
decreasing for n 3; and
1
lim p =0
n ! 1 n ln n

3
by the alternating series test, the series is convergent. To determine whether the
convergence is conditional or absolute, we use the integral test.
X
1
( 1)n X1
1
p = p
n = 3 n ln n n = 1 n ln n

1
As f (n) = p is continuous, positively valued and decreasing for n 3; we can
n ln n
use the integral test.
Z 1 Z 1
1 1 p 1
p dx = p dw = 2 w ln 3 = 1
3 x ln x ln 3 w

X
1
( 1)n
Hence by the integral test, p is divergent, meaning that the original series
n = 3 n ln n
X1
( 1)n
p is conditionally convergent.
n = 3 n ln n

## (b) Prove or disprove the following statements:

X
1 X
1
(i) jan j converges ) an converges.
n = 1 n = 1
X1 X1
(ii) an converges ) jan j converges.
n = 1 n = 1

[10 marks]
X
1 X
1
SOLUTION (i): It is true that jan j converges ) an converges. We will prove
n = 1 n = 1
P
1
this as follows. Let us assume that an is absolutely convergent. By de…nition, this
n = 1
P
1
implies that jan j is convergent. Its associated sequence of partial sums f ng ; n 1
n = 1
is convergent, where we de…ne its nth partial sum to be

## n = ja1 j + ja2 j + ::: jan j :

P
1
Now let us de…ne the nth partial sum of the series an to be
n = 1

sn = a1 + a2 + ::: + an

4
P
1
Here, the associated sequence of partial sums of an is fsn g ; n 1: Now if p =
n = 1
1; 2; 3; ::: Then clearly, n + p > n and

## jsn+p sn j = jan+1 + an+2 + ::: + an+p j

jan+1 j + jan+2 j + ::: + jan+p j
= n+p n = j n+p nj (1)

(*Note: in (1) above, n+p n =j n+p nj since both quantities are positive). Hence
we have that
jsn+p sn j j n+p nj (2)
But we know that f n g ; n 1 is a convergent sequence. Hence it is a Cauchy sequence,
and for any > 0; 9 an n such that j n+p n j < for p = 1; 2; 3; :::

## Hence fSn g ; n 1 is also a Cauchy sequence, which means it is a convergent sequence.

P
1
It follows then that its associated in…nite series an is convergent.
n = 1
X
1 X
1
SOLUTION (ii): It is false to say that an converges ) jan j converges. We
n = 1 n = 1
X1
( 1)n
can prove this by counterexample. is convergent by the alternating series
n = 1
n
test, but
X1
( 1)n X1
1
= the divergent harmonic series.
n = 1
n n = 1
n

3. (a) Use the ratio test and the nth root test to derive two di¤erent expressions for the
X1
radius of convergence R of a power series an xn : Show all your working.
n = 1

[6 marks]
P
1
SOLUTION: Applying the ratio test to cn (x a)n ; we consider
n = 0

## cn+1 (x a)n+1 cn+1

lim = jx aj lim
n ! 1 cn (x a)n n ! 1 cn

5
From the ratio test, we will have absolute convergence for
cn+1
jx aj lim < 1;
n ! 1 cn
i.e. for
1 cn
jx aj < = lim =R
cn+1 n ! 1 cn+1
lim
n ! 1 cn
where
cn
R = lim = radius of convergence.
n ! 1 cn+1
P
1
SOLUTION: Applying the nth root test to cn (x a)n ; we consider
n = 0

1=n
lim jcn (x a)n j = jx aj lim jcn j1=n
n ! 1 n ! 1

## jx aj lim jcn j1=n < 1;

n ! 1

i.e. for
1
jx aj < =R
lim jcn j1=n
n ! 1
where
1
R= = radius of convergence.
lim jcn j1=n
n ! 1

(b) Find the interval of convergence for the power series below. Show all your working
and distinguish between conditional and absolute convergence in relevant cases.
X1
( 2)n (5x 3)2n
(i) p
n = 1
n+2
SOLUTION: Applying the ratio test, we have

## ( 2)n+1 (5x 3)2n+2

p p
n+3 2 n+2
lim n 2n = 2 j5x 3j lim p
n ! 1 ( 2) (5x 3) n ! 1 n+3
p
n+2
= 2 (5x + 3)2

6
Therefore we have absolute convergence, and therefore convergence for
1 1 1
(5x 3)2 < ) p < (5x 3) < p
2 2 2
1
p +3 1
p +3
2
) <x< 2
5 5
1
p +3
2
When x = 5
; the series becomes
2n
1 ( 2)n
X p1 X1
2 ( 1)n
p = p
n = 1
n+2 n = 1
n+2

By the alternating series test, this is convergent since p1 > p1 for all n 1; and
n+2 n+3
1
since lim pn+2 = 0:
n !1
To test whether this convergence is conditional or absolute, consider
X
1
( 1)n X1
1
p = p
n = 1
n+2 n = 1
n+2

X
1
Using the limit comparison test with the divergent p series p1 ; we have
n
n = 1

p1
r
n+2 n
lim = lim =1>0
n !1 p1 n !1 n+2
n

X
1
Hence p1 is divergent, and it follows that the series is conditionally convergent
n+2
n = 1
p1 +3
2
at x = 5
:
1
p +3
2
When 5
; the series becomes
2n
X1 ( 2)n p1 X1
2 ( 1)n
p = p
n = 1
n+2 n = 1
n+2

## which as we saw above is conditionally convergent.

X1
n (2x)2n
(ii)
n = 1
(n)!

7
SOLUTION: Using the ratio test, we have

(n + 1) (2x)2n+2
(n + 1)! (n + 1) n!
lim 2n = (2x)2 lim
n !1 n (2x) n !1 n (n + 1)!

(n)!
(n + 1) n!
= 4x2 lim =0<1
n !1 n (n + 1) n!

[14 marks]